Discordance of Apolipoprotein B, Non-HDL-Cholesterol, and LDL-Cholesterol Predicts Risk of Increased Arterial Stiffness and Elevated Carotid Intima-Media Thickness in Middle-Aged and Elderly Chinese Adults - Jia, Xiaojing; Qi, Yan; Zheng, Ruizhi; Lin, Lin; Hu, Chunyan; Zhu, Yuanyue; Cao, Qiuyu; Wu, Xueyan; Qi, Hongyan; Wei, Ran; Zhang, Yi; Xu, Min; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Apolipoprotein B (apoB) and non-high-density lipoprotein cholesterol (non-HDL-C) have been shown to predict cardiovascular disease (CVD) even in the case of low levels of low-density lipoprotein cholesterol (LDL-C). We aimed to investigate whether the discordance between LDL-C and apoB or non-HDL-C was associated with arterial stiffness and elevated carotid intima-media thickness (CIMT) in middle-aged and elderly adults. Methods: 5,279 Chinese adults free of CVD at baseline were included and followed with mean follow-up of 4.3 years. Arterial stiffness was measured by brachial-ankle pulse wave velocity (baPWV) and pulse pressure (PP). The associations of apoB, non-HDL-C and LDL-C with arterial stiffness or elevated CIMT were examined with logistic regression models using either continuous scales by restricted cubic splines or categories of concordant and discordant values defined by medians. Results: High apoB but not LDL-C was associated with elevated baPWV or PP. High apoB, non-HDL-C and LDL-C were all associated with elevated CIMT (p < 0.05). Individuals with low levels of LDL-C and discordantly high apoB or non-HDL-C compared to those with concordantly low apoB or non-HDL-C demonstrated higher risks of elevated baPWV [ORs (95% CI) of 1.40 (1.03-1.91) and 1.56 (1.12-2.18), respectively] and elevated PP [ORs (95% CI) of 1.61 (1.19-2.18) and 1.55 (1.12-2.15), respectively]. While, discordant high LDL-C with low apoB was associated with increased risk of elevated CIMT (OR, 1.74; 95% CI, 1.13-2.69). Conclusion: Discordance analysis revealed that elevated apoB or non-HDL-C was a better predictor for risk of arterial stiffness, whereas LDL-C for elevated CIMT.